Oh, the places you can go … if you ace calculus: helping minoritized students succeed in undergraduate mathematics - Ibrahim, Amira F. A.; McKellar, Sarah E.; Yates, J. Frank; Shah, Priti (Frontiers in Education, 2025)
Minoritized students tend to have lower undergraduate degree attainment in science, technology, engineering, and mathematics (STEM) than their White and South and East Asian counterparts. According to the Phenomenological Variant of Ecological Systems Theory (PVEST), factors related to historical contexts, systemic processes, and the individual interact to lead to underrepresentation in STEM. However, most of the literature on minoritized STEM students uses a deficit lens and does not consider the role of historical and systemic contexts on these students’ STEM achievement. As a product, current interventions used to increase academic achievement are limited in scope and do not consider the complex interplay between the numerous factors known to influence academic success. By using PVEST as a framework, more holistic interventions that focus on minoritized STEM students’ potential for success can be developed.